Gender-related efficacy of pulmonary surfactant in infants with respiratory distress syndrome: A STROBE compliant study. Issue 17 (April 2018) - Chen, Chen; Tian, Tian; Liu, Li; Zhang, Juan; Fu, Huiling
Abstract : Abstract: Whether gender influences the efficacy of exogenous pulmonary surfactant (PS) for replacement therapy in newborns with respiratory distress syndrome (RDS) has not been well studied yet. Retrospective cohort study design. Data on PS therapy including blood gas, oxygenation function parameters, and therapy results were collected and analyzed from 370 infants diagnosed with RDS in 20 hospitals of the Northwest China Neonatal Collaboration from January 2011 to December 2011. Female infants were more sensitive to PS treatment than males. In multivariate analysis, when adjusted for other variables, an increased initial dose of surfactant significantly reduced mortality risk (OR = 0.98, 95%CI [0.96, 0.99], P  = .002). An interaction between gender and initial dose of PS was observed. In male infants, an increased initial dose of surfactant was correlated with reduced mortality risk (OR = 0.97, 95%CI [0.96, 0.99], P  = 0.005), while in female infants, we failed to found a relationship between the initial dose of surfactant and the risk of mortality (OR = 0.99, 95%CI [0.96, 1.02], P  = .543). Moreover, the effect of surfactant replacement therapy was better for female infants than male infants at initial PS doses <130 mg/kg. Gender influences the efficacy of PS treatment. An increased initial dose of PS should be used in RDS therapy for male infants.